Portuguese football: managing to compete - Simão, Luis Filipe Teixeira (2018)
Football Industry has changed a lot during the last decades and turned into more than just sports or entertaining, into a more complex management challenge. It is now influenced by and influences international environment and organizations, as there is an increasing number of followers and money generation associated with this Sport. For all the complexity and diversity that can be found in the Football business, which cannot be studied all at once, this dissertation’s focus was to find out how competitive the Portuguese Football Clubs are between each other. Although the findings haven’t been compared to other football leagues, it is a starting point to further compare with other international leagues.